2001
DOI: 10.1080/09629350120093722
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules and hyaluronic acid as markers of inflammation, fibrosis and response to antiviral therapy in chronic hepatitis C patients

Abstract: OBJECTIVE: Cell adhesion molecules (intracellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1)) and hyaluronic acid, markers of inflammation and fibrosis were monitored in hepatitis C patients to determine whether changes in plasma levels, during antiviral treatment, can predict long-term response to therapy. METHODS: In 55 patients with chronic hepatitis C virus (HCV), 33 treated with interferon (IFN) and 22 treated with IFN + ribavirin, sera was collected prior to treatment, at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
6
10
0
Order By: Relevance
“…Nevertheless, the lack of significant difference between responders and nonresponders indicates that the persistence of viremia has no influence on PECAM-1 and VCAM-1 expression and therefore they are not a feasible indicator of virus persistence. With respect to sVCAM-1, the results are comparable to Dejica et al [2002] and Granot et al [2001]. Moreover, our study confirmed observations of Granot et al [2001] which revealed the lack of association between sVCAM-1 concentrations and ALT activity during antiviral therapy.…”
Section: Parametersupporting
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, the lack of significant difference between responders and nonresponders indicates that the persistence of viremia has no influence on PECAM-1 and VCAM-1 expression and therefore they are not a feasible indicator of virus persistence. With respect to sVCAM-1, the results are comparable to Dejica et al [2002] and Granot et al [2001]. Moreover, our study confirmed observations of Granot et al [2001] which revealed the lack of association between sVCAM-1 concentrations and ALT activity during antiviral therapy.…”
Section: Parametersupporting
confidence: 94%
“…With respect to sVCAM-1, the results are comparable to Dejica et al [2002] and Granot et al [2001]. Moreover, our study confirmed observations of Granot et al [2001] which revealed the lack of association between sVCAM-1 concentrations and ALT activity during antiviral therapy.…”
Section: Parametersupporting
confidence: 94%
See 2 more Smart Citations
“…Many previous studies reported increased sICAM-1 and sVCAM-1 values in patients with inflammatory diseases of the liver (34)(35)(36)(37)(38). While, elevated serum VCAM-1 in chronic hepatitis have been reported by some authors (39,40).…”
Section: Discussionmentioning
confidence: 86%